What Motivates Internet Financial Reporting in the Public Sector? Case of a Local Government in Indonesia - Dhita Aira Juniantika; Dini Wahjoe Hapsari (Universitas Syiah Kuala, 2020)
Objective – This study aims to examine the influence of local government wealth, local government debt levels, and audit opinions on Internet Financial Reporting (IFR) in districts / cities in West Java Province, Indonesia, during the period of 2014-2018. Design/methodology – This study uses panel data regression analysis. Purposive sampling method is utilized with a total of 65 samples consisting of 13 official sites of district/city governments in West Java Province, Indonesia. The period of this research in total is five years. Results – The results of this study indicate that wealth of local governments, local government debt levels, and audit opinions simultaneously influence IFR at 9.81%. Partially the variable of local government wealth and the debt level of local government do not affect IFR, while the audit opinion variable influences IFR in districts/cities in West Java Province during 2014-2018.